2009
DOI: 10.1007/s00468-009-0352-x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semideciduous hybrid, Q. × turneri (Willd.)

Abstract: Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…For South England, Morecroft et al (2003) reported bud break for Q. robur between mid-April and the beginning of May (doy 102-121; 1996, 1999, 2000). In southern Hesse, Both and Brüggemann (2009) observed bud break in solitary and mature Q. robur at doy 110 and 123 (2006,2007). A warming climate with increased spring-time temperatures could promote earlier bud break (Körner andBasler 2010, Kovats et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For South England, Morecroft et al (2003) reported bud break for Q. robur between mid-April and the beginning of May (doy 102-121; 1996, 1999, 2000). In southern Hesse, Both and Brüggemann (2009) observed bud break in solitary and mature Q. robur at doy 110 and 123 (2006,2007). A warming climate with increased spring-time temperatures could promote earlier bud break (Körner andBasler 2010, Kovats et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…). Thus, a preferential loss of PSI, which usually has much higher activity in intact oak leaves than PSII (Both & Brüggemann and references therein), characterises the medium phase of natural barley leaf senescence, and total disassembly and degradation of the remaining PSII and PSI units occurs only in the final phase. This has also been partially demonstrated by Prakash et al .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to PSI reaction centres, the D1 protein of PSII and Cyt f (a component of the Cyt-b 6 /f complex) was found to degrade more slowly in barley, but the inner light-harvesting complex of light harvesting complex 1 (LHCI) of PSI was still present during late phases of senescence (Miersch et al 2000). Thus, a preferential loss of PSI, which usually has much higher activity in intact oak leaves than PSII (Both & Br€ uggemann 2009 and references therein), characterises the medium phase of natural barley leaf senescence, and total disassembly and degradation of the remaining PSII and PSI units occurs only in the final phase. This has also been partially demonstrated by Prakash et al (2003b) in cucumber using JIP analysis, where there was less efficient electron transfer from Q A À to Q B and beyond during cotyledon senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these taxa are able to survive Western and even Central European winter conditions (cf. Both and Brüggemann 2009) and may become useful in the future for forestation purposes under predicted warmer and dryer climate conditions in Central Europe. In the present study, we analysed winter acclimation of the photosynthetic apparatus in the evergreen Mediterranean Quercus species Q. ilex and Q. suber and their hybrids to deciduous species, i.e.…”
Section: Introductionmentioning
confidence: 98%